2004
DOI: 10.1136/gut.2003.016386
|View full text |Cite
|
Sign up to set email alerts
|

Pancolonic indigo carmine dye spraying for the detection of dysplasia in ulcerative colitis

Abstract: Background and aims: Colonoscopic surveillance for cancer in longstanding extensive ulcerative colitis relies heavily on non-targeted mucosal biopsies. Chromoendoscopy can aid detection of subtle mucosal abnormalities. We hypothesised that routine pancolonic indigo carmine dye spraying would improve the macroscopic detection of dysplasia and reduce the dependence on non-targeted biopsies. Patients and methods: One hundred patients with longstanding extensive ulcerative colitis attending for colonoscopic survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
284
4
26

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(327 citation statements)
references
References 21 publications
13
284
4
26
Order By: Relevance
“…Furthermore, percentage of patients with aneuploidy increases after duration of more than 10 years compared to patients with dysplasia findings that are found more often with disease duration of over 20 years [35]. Other studies confirmed that DNA aneuploidy is stable, widely spread (hence sampling error is minimal), may precede dysplasia (hence represents an early marker), and is evident 10 years after onset of colitis in young patients [23,25,55,63,68,75,76]. In addition to duration, aneuploidy correlates with extent of disease and is associated with total colitis [23,74].…”
Section: Surveillancementioning
confidence: 92%
See 3 more Smart Citations
“…Furthermore, percentage of patients with aneuploidy increases after duration of more than 10 years compared to patients with dysplasia findings that are found more often with disease duration of over 20 years [35]. Other studies confirmed that DNA aneuploidy is stable, widely spread (hence sampling error is minimal), may precede dysplasia (hence represents an early marker), and is evident 10 years after onset of colitis in young patients [23,25,55,63,68,75,76]. In addition to duration, aneuploidy correlates with extent of disease and is associated with total colitis [23,74].…”
Section: Surveillancementioning
confidence: 92%
“…A pre-operative diagnosis of dysplasia of any grade is associated with a 50% probability of associated invasive carcinoma [49]. Dysplasia may be not visible or may be sessile, flat, or minimally elevated and require careful examination to be detected and numerous biopsies are required to confirm its presence [63,68]. Magnifying or high-resolution endoscopy after spraying of dye (indigo carmine, methylene blue, crystal violet) to high light architectural irregularities improves sensitivity of examination of surface mucosa especially when dysplastic changes are subtle, facilitates discovery of dysplasia/CC, and allows targeted biopsies [68][69][70][71].…”
Section: Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…However, the standard strategy of surveillance colonoscopy seems to be associated with risks such as bleeding and lower cost-effectiveness. Several reports have indicated that chromoendoscopy with targeted mucosal biopsies was superior to the standard strategy for detecting dysplasia in IBD patients [59,60]. Although this is a time-saving and cost-effective method, it requires the endoscopist to possess a certain skill and experience level [61].…”
Section: Surveillancementioning
confidence: 99%